The role of duel hydrolysis of soybean on functional properties and protein digestibility: a sustainable approach - Jogi, Nishithkumar; Adusumilli, Somya; Nagesh, Madhukar; Yannam, Sudheer Kumar; Mamatha, Bangera Sheshappa (Frontiers in Nutrition, 2024)
Background Protein hydrolysates derived from food sources contains enormous number of peptides which are composed of amino acid possessess various bioactive properties. However, the use of protein hydrolysates as a nutraceutical is hindered due to their unpleasant flavour. The study aims to enhance the biological activity and palatability of protein hydrolysates. Methodology In the present study, soybean protein hydrolysate (SPH) was prepared using alcalase for 4 h (control). Modification of hydrolysis (MPH) was carried out by reiterating the hydrolysis of the supernatant obtained after 2 h of hydrolysis using an enzyme to 50% of alcalase during each successive hydrolysis. Samples were characterised by their physio-chemical and functional properties. Furthermore, the effect of modification on the protein digestibility and bitterness intensity using e-tongue was studied. The suppressive effect on retrogradation of corn starch was analysed using texture profile analysis. Results The results demonstrated increased protein content by 1.6 and 1.9% in MPH compared to SPH and UNH, respectively. MPH showed 1.5- and 1.6-fold higher DH% than SPH before and after gastrointestinal digestion (p < 0.05). A decrease in molecular weight was found in the order of UNH > SPH > MPH. Nevertheless, MPH displayed significantly higher functional properties (p ≤ 0.05). The hardness of retrograded corn starch was significantly reduced in the MPH (1.21N) than SPH (1.55 N) and UNH (1.81N) compared to control (1.71N) during 7-day storage at 4°C (p ≤ 0.05). E-tongue analysis of MPH showed a 4-fold reduction in bitterness than SPH. Conclusion Modification of hydrolysis of soybean has demonstrated its significance in improved DH% functional properties and palatability. In addition, improved protein digestibility with promising benefits in deferral action on retrogradation of starch over the traditional process of hydrolysis was observed. The outcome of this study contributes to the potential utilisation of MPH as an ingredient in the formulation of nutraceutical products.